2018
DOI: 10.1186/s13007-018-0368-6
|View full text |Cite
|
Sign up to set email alerts
|

Histology-guided high-resolution AP-SMALDI mass spectrometry imaging of wheat-Fusarium graminearum interaction at the root–shoot junction

Abstract: BackgroundFungal pathogens like Fusarium graminearum can cause severe yield losses and mycotoxin contamination of food and feed worldwide. We recently showed its ability to systemically colonize wheat via root infection. However, the molecular response of wheat to Fusarium root rot (FRR) infection and systemic spread is still unknown. As a molecular camera, mass spectrometry (MS) imaging combines label-free and multiplex metabolite profiling with histopathology.ResultsAtmospheric-pressure (AP)-SMALDI-MS imagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 60 publications
3
14
0
Order By: Relevance
“…In the present work we found the presence at 2 dpi of genes related to the glycerophospholipid metabolism pathway, as widely reported previously (van Aarle and Olsson, 2003; Bhandari et al, 2018; Zhang et al, 2020), such as: ethanolamine kinase, acetyltransferase, phosphatidylserine decarboxylase, phosphatidylserine decarboxylase, lysophospholipase NTE1, CDP-diacylglycerol-inositol 3-phosphatidyltransferase, ethanolamine-phosphate cytidylyltransferase, and NTE family protein. Joshi and Mathur in 1987 mentioned that Fox synthesizes up to 26.4% lipids in minimal medium, being glycerophospholipids and triacylglycerols, the latter predominating.…”
Section: Discussionsupporting
confidence: 92%
“…In the present work we found the presence at 2 dpi of genes related to the glycerophospholipid metabolism pathway, as widely reported previously (van Aarle and Olsson, 2003; Bhandari et al, 2018; Zhang et al, 2020), such as: ethanolamine kinase, acetyltransferase, phosphatidylserine decarboxylase, phosphatidylserine decarboxylase, lysophospholipase NTE1, CDP-diacylglycerol-inositol 3-phosphatidyltransferase, ethanolamine-phosphate cytidylyltransferase, and NTE family protein. Joshi and Mathur in 1987 mentioned that Fox synthesizes up to 26.4% lipids in minimal medium, being glycerophospholipids and triacylglycerols, the latter predominating.…”
Section: Discussionsupporting
confidence: 92%
“…It was reported that successful infection of Fusarium species is a complex process that includes adhesion, penetration (through wounds, seeds, stomatal pores) and subsequent colonization within and between cells [34,35]. Consistent with previous reports [36,37], F. fujikuroi isolate CF283 was extensively observed on the aerenchyma, pith, cortex and vascular bundle of both leaf and stem in susceptible Ilpum, whereas this was rarely observed in resistant Zenith.…”
Section: Discussionsupporting
confidence: 88%
“…Besides animal and human tissue analysis, MS imaging has also been adapted to insect and plant tissues (Bhandari, Schott, Römpp, Vilcinskas, & Spengler, 2015;Bhandari, Wang, et al, 2015;Dong et al, 2016). Successful applications of MS imaging include licorice rhizome imaging of flavonoids or saponins (Li, Bhandari, Janfelt, Römpp, & Spengler, 2014), metabolites in maturing and germinating oilseed rape seeds, different tissues in wheat plants, and metabolites illustrating the infection of bread wheat seeds as well as stems with the Fusarium graminearum head blight disease (Bhandari, Wang, et al, 2015;Bhandari et al, 2018). Successful applications of MS imaging include licorice rhizome imaging of flavonoids or saponins (Li, Bhandari, Janfelt, Römpp, & Spengler, 2014), metabolites in maturing and germinating oilseed rape seeds, different tissues in wheat plants, and metabolites illustrating the infection of bread wheat seeds as well as stems with the Fusarium graminearum head blight disease (Bhandari, Wang, et al, 2015;Bhandari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%